Impact of National Board for the Professional Teaching Standards (NBPTS) certification on student achievement - Irvine Belson, Sarah; Husted, Thomas A (Education Policy Analysis Archives, 2015)
A growing number of teachers have undertaken National Board for Professional Teaching Standards (NBPTS) certification training since its inception over twenty-five years ago. Previous empirical research on the impact of NBCTs on student performance has focused on state or district-level exams in individual states and found mixed results. This study examines the relationship between National Board Certified Teachers (NBCTs) and student achievement on the reading and math assessments of the National Assessment of Educational Progress (NAEP). We argue that achievement can be affected both directly by the certified teacher and indirectly as NBCTs provide mentoring to colleagues and assume school leadership positions. This study focuses on a nationally representative assessment to measure student achievement rather than state- or district-level assessment exams. We find that the percentage of National Board certified teachers in a state is positively related to scores on state-level NAEP Reading and Math assessments.